Draft Genome Sequences of Two Glycoalkaloid-Degrading Arthrobacter Strains Isolated from Green Potato Peel - Hennessy, Rosanna C. (Microbiol Resour Announc, 2019)
Here, we report the genome sequences of two Arthrobacter sp. strains isolated from potato and capable of degrading the toxic potato-derived glycoalkaloids (GAs) α-chaconine and α-solanine. Information from the genome sequences will provide insight into the genetic mechanism of GA degradation by these isolates.